General considerations on the care to the elderly victim of abuse - Juan Rafael Cordero Jiménez; Sergio García Cordero; Iris Rodríguez Sánchez; Deysi Santana Castellón; Oraldo Fragoso; Odalis Fernández López (Medisur)
A clear indicator of the magnitude of the aging world population, of which Cuba is not free, is that the average age of the population tends to grow every day. Despite the scientific and technical progress achieved in the field of medical science and health policy efforts to improve the health and welfare of the population, there are still conditions that generate negative phenomena such as violence and its various manifestations, it also affects the elderly. Many need medical care after an act of violence, but most are not identified as such and act is much less reported to the authorities, for which the perpetrators are not prosecuted by law. It is common to find some resistance in its recognition that comes from the clash of such data or suspicion and social representation of the family classic and institutions for the elderly. The prevention and treatment of abuse of older persons in an aging world is everyone's business. Given what is referred to this work is performed in order to provide general comments on senior citizen care mistreated.